Platinum species in the pores of NaX, NaY and NaA zeolites studied using EPR, XAS and FTIR spectroscopies - Akdogan, Yasar; Vogt, Christina; Bauer, Matthias; Bertagnolli, Helmut; Giurgiu, Liviu; Roduner, Emil (Physical chemistry chemical physics : PCCP, 2008)
The results of X-band EPR, X-ray absorption and Fourier transform infrared spectroscopy on Pt(NH(3))(4)(2+) exchanged NaX, NaY and NaA zeolites reveal after oxygen calcination at 573 K that diamagnetic Pt(2+) is not the only product. Calcination provides Pt(3+) cations, but depending on the heating rate, the decomposition of amino groups during calcination also produces hydrogen that reduces Pt(3+) to Pt(2+) and Pt(+). NaX (Si/Al = 1.23) has a more negative framework charge than NaY (Si/Al = 2.31), so Pt(3+) can be stabilized only in NaX, whereas lower oxidation states of Pt such as Pt(+) can be stabilized in both, NaX and NaY, and neither of the paramagnetic Pt cations are stabilized in NaUSY (Si/Al = 3). The autoreduction process allows controlling the number of Pt(3+) and Pt(+) in the NaX zeolite by changing the calcination heating rate: a heating rate of 1.25 K min(-1) gives only Pt(+), but 0.5 K min(-1) gives a Pt(3+)/Pt(+) ratio close to 1. The structure of the support is also important for the synthesis of Pt species. While isolated paramagnetic Pt ions were stabilized in faujasite zeolites (NaX and NaY), a paramagnetic Pt dimer was obtained in a Linde type A zeolite (LTA, Si/Al = 1) by applying the same preparation methods. The fraction of paramagnetic Pt species which were characterized by X-band EPR spectroscopy amounts to 2-18% of the total Pt in the zeolites, the remaining Pt must be diamagnetic.